The parallel resonant DC link inverter: a soft-switching inverter topology with PWM capability - Krogemann, Markus (1997)
Soft-switching inverters have over the last decade received a lot of attention by researchers owing to the reduction or virtual elimination of switching losses that these circuits can achieve. Possible improvements in EMC performance due to the reduced levels of dv/dt have among other advantages triggered the development of a still growing number of zero-voltage or zero-current switching inverter circuits. More recently, the trend seems to have shifted from continuously resonant systems over to quasi-resonant topologies due to advantages in terms of device stresses and PWM compatibility. In this work, continuously resonant as well as quasi-resonant techniques are reviewed. A quasi-resonant circuit will be implemented in a three-phase PWM inverter system controlled by a network of transputers. It will be examined to which degree the working principle of this Parallel Resonant DC Link (PRDCL) inverter affects the PWM compatibility and a suitable PWM strategy will be presented and implemented. The modified PWM technique shows output quality comparable to standard PWM methods while being fully compatible with the operation of the resonant link. The conversion efficiency and EMC performance of a PWM inverter drive based on the PRDCL circuit will be measured and compared to its hard-switched equivalent. It will be shown that improvements over hard-switching inverters are possible. However, the investigation of the PRDCL PWM inverter also reveals a number of drawbacks which limit the achievable switching frequency and adversely affect the conversion efficiency. Despite the many previous publications these problems have generally been overlooked in the past.